Effects of intracameral dexamethasone injection versus topical steroids post phacoemulsification operation - Alaa I. A. Ghonim; Mervat E. Elgharieb; Amr A.-F. Gab-Alla; Ehab M. Moawad (Journal of the Egyptian Ophthalmological Society)
Introduction Cataract surgery is one of the most commonly performed surgeries worldwide, with nearly 20 million cases annually. Ophthalmologists usually use a prophylactic perioperative regimen consisting of topical corticosteroids and nonsteroidal anti-inflammatory drugs to reduce the risk of inflammation. However, patient compliance and other problems concerning administration with elderly patients self-administering medication drops can vary widely and a wide proportion of them fail to comply with a long-term regimen. Aim Evaluation of intracameral dexamethasone injection efficacy and safety versus topical anti-inflammatory eyedrop regimens for postphacoemulsification inflammation for better postoperative management of cataract patients. Methodology A prospective randomized clinical trial. Participants were divided into two groups in group A, dexamethasone sodium-phosphate (0.4 mg/0.1 mL) was injected intracamerally at the end of phacoemulsification surgeries without topical steroids postoperatively. Group B: took the routine postoperative anti-inflammatory steroidal and nonsteroidal eye drop regimen. Results Included the corneal thickness that showed no discernible change between postoperative numbers in both groups. Nevertheless, there was a statistically significant increase in CCT postoperatively in both groups. The intraocular pressure decreased significantly after 1 month of phacoemulsification operation in both groups simultaneously. Postoperative cell density and hexagonality were significantly lower in both groups compared with preoperative values. There was also no significant difference between both groups regarding the anterior chamber cells’ index. Moreover, the Dexamethasone-injected group showed better compliance on the postoperative visits regarding their prescriptions taken after the operation compared with the Prednisone acetate eye drops group. Conclusions Better results regarding the severity of the endothelial damage with the use of a single intraoperative injection post phacoemulsification compared with the group who did not get injected but took postoperative prednisone acetate eye drops. The obligatory single intraoperative injection of dexamethasone has handled the poor compliance of some patients’ post phacoemulsification.